Google searches and medical publication trends since the 2014 US Food and Drug Administration position on power morcellation: Do these translate into patient awareness?. (December 2019) - Liou, N.S.; Mallick, R.; Aref-Adib, M.; Odejinmi, F.
Abstract: Objectives: Our primary objective was to assess patient awareness by observing Google Trends comparing search terms used in relation to morcellation rather than morcellation alone. Our secondary objective was to review trends and locations of publications on leiomyosarcoma and morcellation following the US Food and Drug Administration (FDA) position statement. Study design: To assess Internet trends, we obtained the relative search volume (RSV) for each month from 1 January 2004 to 1 March 2019 from Google Trends using the terms 'fibroid', 'morcellation', and 'fibroid cancer'. RSV ranges from 0 to 100 with 100 being peak popularity for the term, and all other monthly search activity relative to the peak. To assess academic trends, we performed a systematic review of published literature discussing fibroid morcellation within the same time period. We used a two-way independent t -test to compare median RSV, and chi-squared test to compare academic output. P < 0.05 was considered statistically significant. Results: Search volume for 'morcellation' peaked during the FDA statement (RSV 0.5 to 2.9, t = 17.5, p < 0.05) but was not sustained. There is an increase in 'fibroid' activity post-FDA statement (RSV 68.8 to 76.3, t = 3.9, p < 0.05). 'Fibroid cancer' remained static throughout (t = 1.5, p = 0.1 and t=-0.5, p = 0.6). Afro-Caribbean countries had the highest RSV for 'fibroid', whereas 'morcellation' RSV was highest in predominantly Western countries. There was a significant increase in the rate of papers published on the subject following the FDA statement (6.8 vs 55.6 papers per year, 95% CI -53.96 to -43.64, p < 0.0001). No academic papers on morcellation were published from countries with the highest RSV for 'fibroid'. Conclusion: Our study suggests that interest in uterine fibroids has increased since the FDA statement, but the public are perhaps unaware or not concerned of the consequent potential risk of leiomyosarcoma following morcellation. Countries where fibroid interest is highest are not necessarily those that can offer power morcellation. Further studies are required to address how the Internet influences patient choice and informed consent, and how medical professionals can use it to further educate patients on the risks and benefits of laparoscopic myomectomy and power morcellation.